#TITLE_ALTERNATIVE# - NELSON (NIM 102 05 065), CHRIS
Geothermal resource is one of renewable energies possessed by Indonesia in a great deal capacity. Therefore, several events of exploitation activity have been commenced in certain prospect areas. Production activities draw reservoir fluid from aquifer zone and are causing variation in reservoir temperature, enthalpy, and pressure. The changes of these parameters also regulate the rate of production fluid flow. As the consequences, through reservoir modeling with Darcy's Law and mass & energy conservation equation which are separated by finite difference method, the distribution of 2 dimensional temperature, enthalpy, and pressure can be illustrated as a function of time. Moreover, this reservoir simulation also demonstrates the gradient of temperature to the elevation which is evaluated with Indonesian geothermal field's data. Meanwhile, the estimation of reservoir productive period is also performed by applying economical boundary values to the simulation.